Diallel Analysis of Quality and Yield Contributing Traits of Pumpkin (Cucurbita moschata Duch. ex Poir.) (The Agriculturists, 2016)
A 5 X 5 diallel analysis was carried out according to Hayman on quality and yield contributing traits of pumpkin. Five (5) advanced inbreds of pumpkin viz IB 23, IB 40, IB 47, IB 50 and IB 57 were used in this study. The five parents and their F1 hybrids were arranged in a randomized complete block design with three replications for studying the quality and yield contributing traits. Analysis of variance showed significant differences among genotypes for all of the traits except dry matter and fruit yield. Parental mean suggested that all the parents contained recessive alleles with positive effect. In the 5 × 5 diallel set, Wr-Vr graph analysis revealed the presence of allelic interaction in all the characters except fruit length, dry matter, brix percentage and reducing sugar where non-allelic interaction was present.The Agriculturists 2016; 14(1) 15-32